From Cervantes to Kafka. The Judgment of the Author and Manuel Asensi’s “Criticism as Sabotage” (Castilla. Estudios de Literatura, 2019)
The dissolution or “death” of the author is constitutive of the problem of identity, particularly characteristic of cultural studies. With this premise, we will use some notions taken from Manuel Asensi’s “criticism as sabotaje” with the aim of defending that the notion of author not only “survives” its questioning, but it is an element that characteristically insists on appearing through certain gestures, which are essential from a subjective questioning of writing as a communication phenomenon. For this reason we are going to look at ourselves in the mirror of Cervantes’ Don Quixote and, in a special way, in Franz Kafka’s “The Judgment”.
Keywords: author; subject; criticism as sabotage; Cervantes; Kafka